(3GdJWhjQ GdJfXjej hGdNUhUjI GdYQHjI (B/s - (3MehQ ejQZfj, YHO GdYGd MehQs ((3YeGf(B: s (3GdefXeI GdYQHjI ddYdhe GdGOGQjI(B, s, 1987)
(3JLO aj GdcJGH GdEWGQ GdfXQj GdYGe (B: (3GjLGHjGJ hSdHjGJ GdJWhjQ GdJfXjej GdJWhjQ GdJfXjej hhGbY GdHjFI GdYQHjI GdeYGUQI GdJWhjQ GdJfXjej hCaGJ GdacQ GdEOGQj GdYQHjs
Keywords: (3GOGQg GdGYeGds; (3GdEOGQI GdYGeIs; (3GdYdGbGJ GdGfSGfjgs; (3JWhjQ JfXjejs